PENERAPAN LIVING VALUES EDUCATION PROGRAM DALAM MEMBENTUK KARAKTER ANAK USIA 4-6 TAHUN DI TK ISLAM AL- FIKRI BEKASI - Choiriyah Choiriyah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2020)
This study aims to determine: (1) LVEP implementation, and (2) Supporting factors and inhibiting LVEP implementation in TK Islam Al-Fikri. This research is a qualitative research. Subjects are principals, and teachers. Methods of data collection using interviews, observation, and documentation. Data analysis techniques used are data collection, data reduction, data presentation, and conclusions. Data validity techniques use observational persistence, and triangulation of sources and methods. The results show that: (1) Implementation of Living Values Education Program (LVEP) in TK Islam Al-Fikri in the formation of character independence is emphasized on religious and moral values, leadership, and Independence. (2) Supporting factors of LVEP implementation are master trainer, learning method support LVEP, curriculum is flexible, and support from children who are able to cooperate in LVEP implementation. Inhibiting factors include the family's own habits that are less consistent in applying LVEP at home, lack of knowledge of parents about LVEP, LVEP cannot be taught in a short time, differences in student characteristics, there are fast learner and there is a slow learner.